1982
DOI: 10.3758/bf03212294
|View full text |Cite
|
Sign up to set email alerts
|

Distress calling induced by reductions in group size in ducklings reared with conspecifics or imprinting stimuli

Abstract: Peking ducklings were reared for 1-2weeks with either 9 or 12 companions, which were either conspecifics or imprinting stimuli (blocks of foam rubber). They were then tested for their tendency to distress call as the number of companions was reduced systematically. Consistent with prior research, ducklings reared with conspecifics modulated their distress calling as a function of both the number of companions with which they were reared and the number of companions with which they were tested. In contrast, duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Although early studies (Eiserer & Hoffman, 1973) had suggested that the behavioral control of a stationary imprinting object might be comparable in strength to that of the object in motion, the present results (although of marginal significance) join more recent research in indicating relatively weaker control by a stationary imprinting object (Eiserer, 1977;Gaioni & Ross, 1982;Sluckin et aI., 1979). Thus, the present experiment has essentially replicated the findings of Sluckin et al despite basic procedural differences in how the stationary object acquired control.…”
Section: Discussionsupporting
confidence: 73%
“…Although early studies (Eiserer & Hoffman, 1973) had suggested that the behavioral control of a stationary imprinting object might be comparable in strength to that of the object in motion, the present results (although of marginal significance) join more recent research in indicating relatively weaker control by a stationary imprinting object (Eiserer, 1977;Gaioni & Ross, 1982;Sluckin et aI., 1979). Thus, the present experiment has essentially replicated the findings of Sluckin et al despite basic procedural differences in how the stationary object acquired control.…”
Section: Discussionsupporting
confidence: 73%
“…But a limitation of this first ARI experiment in quail was that the robot was not presented very early to the chicks (36 h after hatching), and moreover was present for only 1 h per day with each chick group, because of technical limitations (a single robot was available). As a possible consequence of weak imprinting, chicks did not manifest distress when separated from the robot, contrary to what they do when separated from a real hen, from other chicks, or from an efficient imprinting object (Gaioni andRoss 1982, Ten Cate 1989). In other words, although the animal-robot interaction took place, and successfully modulated the animals' behaviour, we lacked evidence that the robot was truly integrated as a conspecific.…”
Section: Introductionmentioning
confidence: 89%
“…It is an exciting, albeit complex question, that relates to the classic 'filial versus sibling imprinting' issue (see e.g. Gaioni and Ross 1982). Here are a few issues:…”
Section: Social Status Of the Robotmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of movement on the attractiveness of a stimulus is so profound that this movement was even suggested to constitute an UCS for the imprinting process, with the static features of the stimulus as the CS (e.g. HOFFMAN et al 1970;EISERER 1980;GAIONI & Ross 1982). But although the effect Stimulus Movement, Hen Behaviour and Filial Imprinting 289 of movement as an enhancer of imprinting is well known, surprisingly little attention has been given to a more precise analysis of the effect of various types of movement, and, in particular, to comparing the effect of artificial movement with that of the natural behaviour of a living hen.…”
Section: Introductionmentioning
confidence: 99%